Current state of macrozoobenthos in Lake Munozero - Sidorova A.I.; Georgiev A.P. (Трансформация экосистем)
The article presents the study results (summer-autumn of 2017–2022) of macrozoobenthos in the Lake Onega basin (Lake Munozero, Republic of Karelia). The average biomass of macrozoobenthos in the littoral zone made up 3.6 g/m2, while in the deep-water part of the lake – 2.7 g/m2. The average number of benthic organisms in the coastal and profundal zones of the reservoir reached 2.7 and 1.1 thous. ind./m2, respectively. Gastropods (34.9%) and isopods (22.4%) played a significant role in the formation of macrozoobenthos biomass in the coastal zone of the lake. In the deep part of the reservoir, amphipods, valuable in terms of food resources, developed in large numbers. With a population of 1 thousand ind./m2 (89.5%), their biomass accounted for 2.7 g/m2 (98% of the total). Thus, amphipods formed the feed base for fish in the profundal zone. Insect larvae, mainly of the family Chironomidae, provided the taxonomic richness of the lake macrozoobenthos.